2018
DOI: 10.1002/ajmg.a.40508
|View full text |Cite
|
Sign up to set email alerts
|

A novel ASPH variant extends the phenotype of Shawaf‐Traboulsi syndrome

Abstract: Shawaf-Traboulsi syndrome (or Traboulsi syndrome; MIM 601552) is an infrequently reported entity characterized by a typical face (long face, large nose, convex nasal ridge, underdeveloped malae, crowded teeth, retrognathia), skeletal signs (long and slender fingers, sometimes pectus deformation and hypermobile joints), and ectopia lentis with conjunctival blebs, shallow anterior chamber and iridocorneal adhesions. The entity is caused by homozygous variants in ASPH. Here, we report on a boy with the clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“… 10 The upregulation of AspH and its translocalization from the endoplasmic reticulum (ER) membrane to the cell surface in cancer cells correlates with enhanced cell motility and metastatic spread resulting in a reduced lifespan of the affected patients. 11 , 12 Studies on naturally occurring mutations of human AspH presumably resulting in inactive AspH (Traboulsi syndrome) 13 , 14 , 15 , 16 and animal models 8 , 17 , 18 suggest that AspH might affect cell motility through the notch signalling pathway. Despite the combined evidence suggesting that AspH is a promising medicinal chemistry target for the development of small-molecule-based cancer therapeutics, comparatively few AspH inhibition studies using small-molecules are reported, with most of these relying either on the use of likely non-selective 19 , 20 or partially selective 21 small-molecules or on the use of l -ascorbic acid (LAA)-derived small-molecules.…”
Section: Introductionmentioning
confidence: 99%
“… 10 The upregulation of AspH and its translocalization from the endoplasmic reticulum (ER) membrane to the cell surface in cancer cells correlates with enhanced cell motility and metastatic spread resulting in a reduced lifespan of the affected patients. 11 , 12 Studies on naturally occurring mutations of human AspH presumably resulting in inactive AspH (Traboulsi syndrome) 13 , 14 , 15 , 16 and animal models 8 , 17 , 18 suggest that AspH might affect cell motility through the notch signalling pathway. Despite the combined evidence suggesting that AspH is a promising medicinal chemistry target for the development of small-molecule-based cancer therapeutics, comparatively few AspH inhibition studies using small-molecules are reported, with most of these relying either on the use of likely non-selective 19 , 20 or partially selective 21 small-molecules or on the use of l -ascorbic acid (LAA)-derived small-molecules.…”
Section: Introductionmentioning
confidence: 99%
“…These microduplications correlated to Laurin–Sandrow syndrome and Haas‐type polysyndactyly, according to the ZRS region length (Lohan et al, ). Moreover, Peruvian geneticists of INSN described unique cases of pterygium‐digital keloid dysplasia (Abarca et al, ), H syndrome (Abarca Barriga, Trubnykova, Polar Córdoba, Ramos Diaz, & Aviles, ), van der Knaap syndrome (Hamilton et al, ), and Shawaf‐Traboulsi syndrome (Abarca Barriga et al, ). Last, international collaboration permitted reports of two common genetic syndromes—that is, Noonan (Kruszka et al, ) and Williams‐Beuren (Kruszka et al, )—with clinical geneticists of the National Human Genome Research Institute of The National Institutes of Health; and with other geneticists of different sites in the globe, contributing to the worldwide clinical genetics area.…”
Section: Healthcare Services Of Genetics and Genomicsmentioning
confidence: 99%
“…Mutations in the AspH gene can have consequences in lens instability ( 14 ). Traboulsi syndrome is an extremely rare ophthalmological disorder that is caused by homozygous variants in the AspH gene, wherein facial dysmorphism, lens dislocation, anterior segment abnormalities, and spontaneous filtering blebs are observed ( 15 17 ). Loss of murine hydroxylase activity is associated with increased intestinal tumor incidence and developmental defects similar to those caused by altered Notch signaling ( 18 ).…”
Section: Introductionmentioning
confidence: 99%